2007
DOI: 10.1097/fpc.0b013e3280115e63
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of the DNA repair gene XPD/ERCC2 alter mRNA expression

Abstract: Our results provide novel mechanistic explanations for epidemiological studies linking these SNPs to elevated cancer risk and emphasize the importance of comprehensively investigating the effect of both synonymous and nonsynonymous SNPs as risk modifiers by considering their potential effects on gene expression, protein translation and functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 43 publications
3
41
1
1
Order By: Relevance
“…It has been identified that the XPD Lys751Gln polymorphism may potentially reduce XPD mRNA levels by affecting mRNA stability as well as influencing XPD function by evoking alterations in protein-folding properties (Wolfe et al, 2007). However, no significant association between the XPD Lys751Gln polymorphism and XPD protein expression levels has been observed (Lai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that the XPD Lys751Gln polymorphism may potentially reduce XPD mRNA levels by affecting mRNA stability as well as influencing XPD function by evoking alterations in protein-folding properties (Wolfe et al, 2007). However, no significant association between the XPD Lys751Gln polymorphism and XPD protein expression levels has been observed (Lai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Functional polymorphisms in these NER genes have been reported that may affect DNA repair capacity and influence the efficacy of treatments using DNA-damaging agents (Wolfe et al 2007;Au et al 2003;Lunn et al 2000). In the ERCC1 gene, the ERCC1 8092 C/A (rs3212986) polymorphism occurs with relatively high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms are associated with variations in adduct levels (Benhamou and Sarasin 2005), chromosomal aberrations (Au et al 2004;Affatato et al 2004) and mRNA expression levels in lymphocytes (Wolfe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Some polymorphisms have been described as important for the activity of platinum drugs, the most common of which occur in DNA repair and glutathione S-transferase (GST) genes. By their effects on mRNA levels or mRNA stability, polymorphisms in genes for DNA repair (for example, ERCC1 19007 T4C and 8092 C4A, XPD Asp312Asn and Lys751Gln) can modulate the total DNA repair capacity [5][6][7][8] and influence the removal of platinum-DNA adducts, the persistence of which underpins the antitumor potential of platinum drugs. 9 GSTs, especially GSTP1, can substantially limit the amount of free platinum drugs available for interaction with DNA, by catalyzing their binding to tripeptide glutathione, one of the most abundant molecules in cells.…”
Section: Introductionmentioning
confidence: 99%